Peran Bantuan Hukum Bagi Masyarakat Tidak Mampu Oleh Pos Bantuan Hukum (Posbakum) Di Pengadilan Agama Bantul - Miftahul Huda Huda (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
The existence of Posbakum (Legal Aid Post) as one of legal aid services in Religious Court Bantul that has helped the community more particularly for the underprivileged community in the trial process by referring to PERMA No.1 /2014 on “the guidelines in giving the legal services for the underprivileged community”. However, whether the service of Posbakum has really applied PERMA in accordance to its enforceability such as giving service in making legal documents, legal advices, consultation, and information and the provision of socialization related to law firm is still questioning. This is a field research using the empirical juridical study approach. Based on the results, it was found that the position of Posbakum in PERMA No. 1/2014 was well enforced. The Religious Court bantul legal aid post as a provider of free legal services, such as providing information, consulting or legal advice, assisting in the preparation of required legal documents. Because people who arrive at Posbakum get free legal services, both from consultations to making the required legal documents. During the Covid-19 pandemic, Posbakum continue to provide services online or offline with implementing health protocols, namely: Implementing physical distancing, Obligation to wear a mask, Urge to wash hands, Installing a transparent hijab, Limiting service hours. So that judicial process and services to justice seekers can still run according to the procedure.